Design / preparation method and application of corrosion-resistant multi-principal-element binding phase hard alloy
By establishing a phase diagram thermodynamic database and Pourbaix diagram calculation, multi-main alloys are selected as bonding phases, and the phase composition and heat treatment parameters of cemented carbide are optimized, which solves the problem of corrosion and dissolution of cemented carbide in different corrosion environments, and improves corrosion resistance and extends service life of cemented carbide.
Patent Information
- Application Number
- CN202510033714.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-10-31
- Filing Date
- 2025-01-08
- Publication Date
- 2025-05-09
- Estimated Expiration
- 2045-01-08
AI Technical Summary
Existing cemented carbides are prone to corrosion and dissolution of bonded phases in different corrosion environments, resulting in damage to the overall structural integrity, reduced strength and premature fracture of the carbide skeleton, affecting the service life of drilling components.
By establishing a phase diagram thermodynamic database and Pourbaix diagram calculation, the corrosion products and immune regions of the cemented carbide system in the target corrosive service environment are predicted, and the multi-main alloys are selected as the bonding phase to optimize the phase composition and heat treatment parameters of the cemented carbide.
The corrosion resistance performance of cemented carbide is improved, the service life of drilling parts is extended, the preparation efficiency of cemented carbide is improved, and the intrinsic connection between composition-structure-performance is established.
Smart Images

Figure CN119964695A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of cemented carbide, and in particular to a design / preparation method and application of a corrosion-resistant multi-principal-element bonding phase cemented carbide. Background Art
[0002] At present, the increasing demand for energy has promoted deep drilling activities in the continental and oceanic crusts, posing new challenges to the durability of drilling tools. Cemented carbide is widely used in marine drilling equipment due to its high hardness, wear resistance, heat resistance, and corrosion resistance. For typical WC-Co cemented carbide, excessive corrosion may lead to damage to the overall structural integrity due to the damage of the bonding phase, resulting in reduced strength and premature fracture of the carbide skeleton. Therefore, optimizing the corrosion resistance of cemented carbide is crucial to ensure the service life of drilling components. The corrosion behavior of cemented carbide is affected by the phase structure and chemical composition of the metal bonding phase. In recent years, multi-principal element alloys have attracted much attention due to their excellent corrosion resistance due to the combination of the benefits of controlled phase structure (such as FCC) and chemical composition (such as Cr) for surface passivation. CoCrNi multi-principal element alloy has good corrosion resistance and strong toughness, but its application as a bonding phase in cemented carbide has not been studied. As a traditional bonding phase, Co can play a good role in wettability and bonding, Ni has greater ductility and corrosion resistance, Cr has better oxidation resistance and corrosion resistance, and the CoCrNi alloy bonding phase has good wettability with the hard phase WC. Therefore, it is considered to introduce CoCrNi multi-element alloy as a bonding phase into the cemented carbide system to improve the corrosion resistance of cemented carbide.
[0003] The corrosion behavior of cemented carbide is also related to the corrosive medium. Different corrosive environments will cause differences in corrosion mechanisms and corrosion products. It is well known that for the corrosion of typical WC-Co cemented carbide, Co is easily soluble in acidic and neutral solutions, while WC is relatively stable and not prone to corrosion. In alkaline solutions, there is no consensus on the dissolution process of Co and WC. In addition, the formation of passivation film in the corrosive medium will also affect the corrosion resistance of cemented carbide. In the preparation process of corrosion-resistant cemented carbide, it is difficult to obtain satisfactory results only by adding elements. Therefore, it is very important to rationally design cemented carbide by introducing a new multi-element bonding phase and combining theoretical calculations. Summary of the invention
[0004] In view of the deficiencies in the prior art, the object of the present invention is to provide a design / preparation method and application of a corrosion-resistant multi-principal-element binder phase cemented carbide.
[0005] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention includes:
[0006] In a first aspect, the present invention provides a design method for a corrosion-resistant multi-principal-element binder phase cemented carbide, comprising:
[0007] Obtaining a target corrosive service environment, and formulating a target cemented carbide system according to the target corrosive service environment, wherein the target cemented carbide system includes a hard element corresponding to hardness and a bonding element corresponding to bonding;
[0008] Establishing a phase diagram thermodynamic database of the target cemented carbide system;
[0009] According to the phase diagram thermodynamic database, a Pourbaix diagram is calculated for the target cemented carbide system to obtain the inferred corrosion products of the target cemented carbide system under the target corrosive service environment and the immune zone and the passivation zone corresponding to the inferred corrosion products, and a multi-principal alloy is selected as a bonding phase from the bonding elements;
[0010] According to the phase diagram thermodynamic database, a phase diagram is calculated for the target cemented carbide system to obtain phase composition and phase parameters, wherein the phase composition includes the ratio of the bonding elements and the ratio of the hard phase to the bonding phase, and the phase parameters include heat treatment temperature;
[0011] The multi-principal component alloy, phase composition and phase parameters are used as design outputs of the corrosion-resistant multi-principal component bonding phase cemented carbide.
[0012] In a second aspect, the present invention further provides a method for preparing a corrosion-resistant multi-principal-component binder phase cemented carbide, comprising:
[0013] The above design method is used to obtain the design output in the target corrosive service environment;
[0014] According to the design output, a corrosion-resistant multi-principal-component bonding phase cemented carbide is prepared.
[0015] In a third aspect, the present invention also provides the use of the corrosion-resistant multi-principal-component bonding phase cemented carbide prepared by the above preparation method in the manufacture of marine drilling equipment.
[0016] Based on the above technical solution, compared with the prior art, the beneficial effects of the present invention at least include:
[0017] The technical solution provided by the present invention is to establish a thermodynamic database and a method for calculating the Pourbaix diagram and phase diagram based on the electrochemical Nernst equation; predict the possible corrosion products and the corrosion immune zone and passivation zone, and verify them through micro-area electrochemical experiments. According to the basic characteristics of cemented carbide electrochemical corrosion with different bonding phases, the optimal multi-principal bonding phase is selected to match the hard alloy, thereby obtaining a multi-principal bonding phase WC-based cemented carbide with excellent corrosion resistance. The design method provided can clarify the element composition and phase structure in the bonding phase, use the Pourbaix diagram and phase diagram to guide the design of a reasonable corrosion-resistant cemented carbide preparation process, improve the preparation efficiency of the cemented carbide, and establish the intrinsic relationship between the composition, structure and performance of the corrosion-resistant cemented carbide; use micro-area electrochemical test verification to provide a basis for the efficient design of cemented carbide with improved corrosion resistance, and guide the design and preparation of high-performance corrosion-resistant multi-principal cemented carbide from the perspective of corrosion product result prediction.
[0018] The above description is only an overview of the technical solution of the present invention. In order to enable those skilled in the art to more clearly understand the technical means of the present application and implement them according to the contents of the specification, the following is a description of the preferred embodiments of the present invention in conjunction with detailed drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 It is a schematic diagram of the process of designing and verifying a corrosion-resistant multi-principal-element bonding phase cemented carbide provided by a typical implementation case of the present invention;
[0020] Figure 2a It is a Pourbaix diagram of a W-Co system at different electrode potentials and pH values provided by a typical embodiment of the present invention;
[0021] Figure 2b It is a Pourbaix diagram of a W-Co-Cr-Ni system at different electrode potentials and pH values provided by a typical embodiment of the present invention;
[0022] Figure 3 It is a vertical cross-sectional diagram of the composition of the W-Co-Cr-Ni-C system at different temperatures according to the carbon content of the system provided by a typical implementation case of the present invention;
[0023] Figure 4a -g is a composition and structure diagram corresponding to the TEM of a WC-CoCrNi system cemented carbide prepared in a typical embodiment of the present invention;
[0024] Figure 5a This is a SVET test diagram of a WC-CoCrNi system in 3.5% NaCl at pH=10 provided by a typical implementation case of the present invention;
[0025] Figure 5b This is a typical embodiment of the present invention, provided by a comparative example of a classic WC-Co system cemented carbide sample in 3.5% NaCl at pH = 10.
[0026] Figure 5c This is a LEIS test diagram of a WC-CoCrNi system in 3.5% NaCl at pH=10 provided by a typical implementation case of the present invention;
[0027] Figure 5d This is a LEIS test chart of a comparative classic WC-Co system cemented carbide sample in 3.5% NaCl at pH=10 provided by a typical implementation case of the present invention. DETAILED DESCRIPTION
[0028] In view of the deficiencies in the prior art, the inventor of this case has proposed the technical solution of the present invention after long-term research and extensive practice. The technical solution, its implementation process and principle will be further explained as follows.
[0029] In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention may also be implemented in other ways different from those described herein. Therefore, the protection scope of the present invention is not limited to the specific embodiments disclosed below.
[0030] In the field of cemented carbide preparation, some existing technologies use traditional enumeration methods to prepare corrosion-resistant cemented carbide with excellent performance. For example, the Chinese invention patent with publication number CN101974715A discloses a WC-Co cemented carbide and its preparation method. The method is mainly for WC cemented carbide, in which the traditional bonding phase Co is used, mixed with a small amount of Y powder, which provides a reference for the preparation process of cemented carbide, but cannot systematically adjust or redesign the corresponding alloy for different corrosion-resistant environments. The Chinese invention patent with publication number CN102031436A discloses a method for improving the corrosion resistance of WC-Co cemented carbide, which improves the corrosion resistance by introducing rare earth components, but does not explain the material design, and the detection method for corrosion is relatively traditional, and does not reveal the corrosion mechanism and the essential reasons for the improvement of corrosion resistance.
[0031] Therefore, based on the existing research in this field, the present invention realizes the integration of WC cemented carbide material system design and preparation by combining theoretical calculations with micro-area characterization methods, aiming to achieve low-cost, efficient and rapid material design.
[0032] The purpose of the present invention is to provide a design and verification method for a corrosion-resistant multi-principal-element bonding phase cemented carbide.
[0033] Cemented carbide is mainly composed of hard phase and binder phase. When cemented carbide composite materials are in a corrosive service environment, due to the difference in potential between the binder phase and the hard phase, the two are prone to galvanic corrosion, which causes the corrosion and dissolution of the binder phase. The hard phase's role as a skeleton support is weakened, which ultimately affects the performance match between the hard phase and the binder phase, leading to failure. Corrosion-resistant multi-principal alloys are introduced as binder phases to improve the overall corrosion resistance of cemented carbide and improve the shortcomings of traditional cemented carbide in corrosive environments. The Pourbaix diagram is a reliable tool for studying the corrosion characteristics of alloys. Using Pourbaix calculations to guide experiments can help speed up material design and make up for the shortcomings of intelligent design of corrosion-resistant cemented carbide materials.
[0034] In addition, the use of CALpHAD method to calculate the phase diagram can further accelerate the design of cemented carbide materials. The phase structure of the binder phase will also affect the corrosion resistance. The phase diagram guides the reasonable phase interval and sintering temperature of the sample preparation process;
[0035] Based on the above technical concept, see Figure 1 As shown, an embodiment of the present invention provides a design method for a corrosion-resistant multi-principal-element bonding phase cemented carbide, which comprises the following steps:
[0036] Obtaining a target corrosive service environment, and formulating a target cemented carbide system according to the target corrosive service environment, wherein the target cemented carbide system includes a hard element corresponding to hardness and a bonding element corresponding to bonding;
[0037] Establishing a phase diagram thermodynamic database of the target cemented carbide system;
[0038] According to the phase diagram thermodynamic database, a Pourbaix diagram is calculated for the target cemented carbide system to obtain the inferred corrosion products of the target cemented carbide system under the target corrosive service environment and the immune zone and the passivation zone corresponding to the inferred corrosion products, and a multi-principal alloy is selected as a bonding phase from the bonding elements;
[0039] According to the phase diagram thermodynamic database, a phase diagram is calculated for the target cemented carbide system to obtain phase composition and phase parameters, wherein the phase composition includes the ratio of the bonding elements and the ratio of the hard phase to the bonding phase, and the phase parameters include heat treatment temperature;
[0040] The multi-principal component alloy, phase composition and phase parameters are used as design outputs of the corrosion-resistant multi-principal component bonding phase cemented carbide.
[0041] As a typical application example, the process of the above overall design method can be implemented in the following steps:
[0042] (1) Select the type of multi-principal alloy binder phase elements according to the corrosive service environment and determine the target cemented carbide system;
[0043] (2) establishing a phase diagram thermodynamic database of the target cemented carbide system;
[0044] (3) performing Pourbaix diagram calculation based on the thermodynamic database to obtain a relationship diagram between the potential and pH of the corresponding system and an immune zone and a passivation zone corresponding to the corrosion product;
[0045] (4) Based on the constructed thermodynamic database of cemented carbide system, phase diagram calculation is performed to obtain the composition ranges corresponding to different phase compositions.
[0046] In a more specific application example, taking the WC-Co-Cr-Ni quinary system as an example, the embodiment of the present invention is directed to a corrosion-resistant WC cemented carbide system, which includes a WC hard phase with excellent toughness and a CoCrNi bonding phase with excellent corrosion resistance, thereby forming a quinary system thermodynamic database containing five elements: W, C, Co, Cr, and Ni. Based on the established database and combined with the CALpHAD method, a corrosion-resistant WC cemented carbide system is designed.
[0047] Regarding the specific optional range of elements, in some embodiments, the hard elements include any combination of W, Ti, C, and N.
[0048] In some embodiments, the bonding element includes any combination of Co, Cr, Ni, Fe, Al, and Mn.
[0049] In addition, regarding how to guide the design based on the Pourbaix diagram and the phase diagram, in some embodiments, the selection rules of the multi-principal alloy specifically include:
[0050] Select the required hard phase and binder phase element types and proportions according to the applicable environment;
[0051] The immune area and passivation area of the system are obtained by calculating the Pourbaix diagram;
[0052] The immune zone is the non-corrosion area (blue) of the thermodynamically stable state below the equilibrium line of the Pourbaix diagram. The larger the immune zone, the stronger the material's ability to resist corrosion and the better its corrosion resistance.
[0053] The passivation zone is the area where corrosion products of oxides and hydroxides are generated (orange). Since an insoluble and dense protective film is formed on the metal surface, the passivation zone protects the sample surface to a certain extent and can also greatly reduce the corrosion of the metal. The large area of the passivation zone (the passivation film can be generated in an area with a wider range of pH and potential, which is more conducive to protecting the sample surface) is beneficial to the corrosion resistance of the material;
[0054] The Pourbaix diagrams of different systems were compared to predict their corrosion resistance, and one or more samples with relatively larger immune and / or passive zones were selected.
[0055] In some embodiments, the selection rules of phase composition and phase parameters specifically include:
[0056] Calculate the phase diagram according to the corresponding system composition;
[0057] Based on the calculation results of the phase diagram, the normal structure WC+γ of cemented carbide is selected to avoid the adverse effects of abnormal structures (carbide, graphite phase) on the performance of cemented carbide;
[0058] Since the phase diagram calculation results show that there is no region containing only WC+γ, the C content is closest to the transition line from the carbon-poor phase to the graphite phase to avoid the influence of carbides as much as possible;
[0059] The liquidus line of the corresponding system is determined based on the phase diagram calculation results to guide the determination of the sintering temperature.
[0060] In addition, regarding the process of establishing the Pourbaix diagram and the phase diagram, in some embodiments, the process of establishing the phase diagram thermodynamic database may specifically include:
[0061] Acquiring thermodynamic data of a low-element system, wherein the elements in the low-element system are part of the elements in the target cemented carbide system;
[0062] Establishing a thermodynamic model to calculate the Gibbs free energy of multiple phases in the low-element system;
[0063] All calculation results are integrated and expanded to form a phase diagram thermodynamic database of the target cemented carbide system.
[0064] Still taking the WC-Co-Cr-Ni quinary system as an example, step (2) above may specifically include:
[0065] (2-1) collecting thermodynamic data of all pure component, binary and ternary systems included in the target cemented carbide system;
[0066] (2-2) Evaluating and screening the collected thermodynamic data;
[0067] (2-3) Based on reliable experimental phase diagrams and thermodynamic information, select appropriate thermodynamic models to describe the Gibbs free energy of different phases;
[0068] (2-4) By integrating the above-evaluated thermodynamic parameters and making reasonable extrapolations, a self-consistent thermodynamic database of the Co-Cr-Ni-WC quinary system phase diagram is obtained.
[0069] In the above process, firstly, the thermodynamic databases of pure component, binary system, ternary system and other systems of the target cemented carbide system are collected; then, the system phase diagram is drawn from low to high based on the phase diagram calculation method, and compared and corrected. After evaluation and optimization, all the above parameters are organically integrated until a reliable Co-Cr-Ni-WC five-element thermodynamic database of the target cemented carbide is obtained.
[0070] In some embodiments, the process of calculating the Pourbaix diagram specifically includes:
[0071] Importing the phase diagram thermodynamic database into the calculation software, using the point calculation module to input the target composition of the target cemented carbide system, and obtaining the chemical potential corresponding to each element in the target composition;
[0072] Based on the Gibbs free energy of pure elements, the energy difference of each element in the target component is obtained through the electrochemical reaction equation and the Nernst equation and converted into a potential difference value;
[0073] A multivariate Pourbaix diagram is obtained based on superimposed pure element Pourbaix diagrams, the change in Gibbs free energy caused by alloying is calculated, and the immune area and the passivation area of the multivariate Pourbaix diagram are delineated.
[0074] The specific exemplary process of the above steps is:
[0075] Calculating the single element Pourbaix diagram involved in the target cemented carbide system by combining the thermodynamic database and the Pourbaix diagram calculation software;
[0076] The calculation process is to select the elements involved in the system, input the electrode potential range and temperature parameters, and output all possible products;
[0077] The single element Pourbaix diagram is generated after the product is selected and optimized;
[0078] The system thermodynamic database is imported into the phase diagram calculation software, and the target component is input using the point calculation module to obtain the chemical potential corresponding to the single element of the target component. Based on the pure element Gibbs free energy, the energy difference of each element in the target component is obtained through the electrochemical reaction equation and the Nernst equation and converted into a potential difference value;
[0079] The Nernst equation is expressed as:
[0080] For any electrochemical reaction equation aA+bB=cC+dD
[0081]
[0082] Among them, E θ represents the standard electrode potential; R represents the gas constant 8.31441 J / (K.mol); T represents the temperature; n represents the number of electron transfers in the electrode reaction; F represents the Faraday constant 96.487 kJ / (V.mol);
[0083] The calculated potential difference value is brought into the Pourbaix diagram for correction;
[0084] The Pourbaix diagram of the target system is obtained by superimposing the different single-element Pourbaix diagrams obtained by the above method.
[0085] In addition, in step (4) described above, the phase diagram of the target cemented carbide system can be calculated in combination with the thermodynamic database and the phase diagram calculation software;
[0086] Then, the composition intervals of different bonding phases of the target cemented carbide system under different conditions are calculated based on the phase diagram, such as Figure 2a and Figure 2b As shown;
[0087] Then, according to the relationship between the phase structure and the composition and temperature obtained from the phase diagram calculation results, the liquid phase sintering temperature and the carbon content range of the system are determined, such as Figure 3 As shown;
[0088] Finally, a cemented carbide sample was prepared by a powder metallurgy method based on the phase structure.
[0089] The structure of the prepared cemented carbide samples was verified and the corrosion electrochemical properties were tested, and finally the composition and preparation conditions of a corrosion-resistant multi-component bonding phase cemented carbide were determined.
[0090] The phase diagram intuitively reflects the relationship between the composition, temperature and structure of the reaction material. Starting from the expected structure and performance of the material, the phase relationship of the target cemented carbide system under different sintering temperatures and carbon contents is obtained based on the phase diagram calculation method. By selecting a reasonable composition range, the ideal corrosion-resistant cemented carbide can be efficiently screened.
[0091] In some embodiments, the design method may further include the following verification steps:
[0092] Preparing a verification sample according to the multi-principal alloy, phase composition and phase parameters by powder sintering;
[0093] The microstructure and corrosion pattern of the verification samples are characterized to verify the effectiveness of the design output.
[0094] In some embodiments, the characterization method of the microscopic morphology includes transmission electron microscopy observation, and the characterization method of the corrosion mode includes micro-area electrochemical experiments. TEM analysis of the designed and prepared samples reveals the rationality of the design of the sample composition structure, and the micro-area electrochemical experiment reveals the improvement of the electrochemical corrosion performance of the prepared samples from a microscopic scale, thereby guiding the development and design of corrosion-resistant cemented carbide. For example, based on the thermodynamic database phase diagram calculation prediction to obtain the composition and structure of the cemented carbide system, combined with TEM means to verify the composition and structure of the prepared cemented carbide system; use micro-area electrochemical testing methods to measure the galvanic corrosion relationship between the hard phase and the bonding phase, experimentally verify the galvanic corrosion tendency, and reveal the improvement of the corrosion resistance of the sample.
[0095] A second aspect of the embodiment of the present invention further provides a method for preparing a corrosion-resistant multi-principal-component binder phase cemented carbide, which comprises the following steps:
[0096] Using the design method provided by any of the above embodiments to obtain a design output in a target corrosive service environment;
[0097] According to the design output, a corrosion-resistant multi-principal-component bonding phase cemented carbide is prepared.
[0098] In some embodiments, the preparation method may specifically include:
[0099] preparing a binder phase powder and a hard phase powder according to the design output;
[0100] The mixed powder is prepared according to the ratio of the hard phase and the binder phase outputted in the design, and ball milling and pressing are performed to obtain a sintered hard alloy block;
[0101] The cemented carbide block sintered blank is subjected to vacuum sintering to obtain the corrosion-resistant multi-principal-element bonding phase cemented carbide.
[0102] As a specific example, the design and preparation process of a complete corrosion-resistant multi-principal binder phase cemented carbide includes the following steps:
[0103] (1) Selecting a suitable multi-principal alloy as the binder phase based on the Pourbaix diagram;
[0104] (2) Determine the appropriate carbon content and sintering temperature based on the phase diagram;
[0105] (3) mixing a binder phase powder and a hard phase powder to obtain a mixed powder;
[0106] (4) wet-milling the mixed powder and pressing the mixed powder to obtain a cemented carbide block sintered blank;
[0107] (5) The cemented carbide samples were obtained by vacuum sintering.
[0108] Specific forming and sintering processes such as:
[0109] By adding the binder phase powder and the hard phase powder to high energy ball milling, the powder is selected as WC, CoCrNi, Co, C powder;
[0110] The pre-mixed powder is wet-milled, alcohol is used as the milling medium during the wet-milling mixing process, the ball-to-material mass ratio is 8:1N12:1, and the milling time is 10-20 hours;
[0111] The ball-milled powder is molded and sintered, the ball-milled mixed slurry is dried and sieved, and then pressed under a pressing pressure of 120 to 180 MPa;
[0112] The maximum liquid phase sintering temperature is determined by the phase diagram and is kept at this temperature for 0.5 to 3 hours;
[0113] The complete typical preparation process is as follows:
[0114] WC, CoCrNi and Co powders were used to prepare cemented carbide, wherein the ratio of cemented carbide powder to binder phase powder was 8:2;
[0115] The mixed powder is added to the molding agent paraffin; and placed in a hard alloy ball mill, wherein the ball-to-material mass ratio is 10:1, and the ball milling medium alcohol is added, and the ball milling time is 16 hours;
[0116] The pressing pressure in the subsequent pressing process was 150 MPa;
[0117] The maximum sintering temperature was determined to be 1450°C according to the phase diagram and kept at that temperature for 90 minutes to obtain a cemented carbide sample.
[0118] After preparing the samples, the composition and structure of the corresponding cemented carbide system can be predicted based on the constructed thermodynamic database of the cemented carbide system. Combined with the TEM characterization results of the prepared cemented carbide, the rationality of the thermodynamic database in predicting the cemented carbide system can be verified, thereby promoting the efficient design of the cemented carbide system.
[0119] The required electrochemical test solution pH and electrochemical test potential are selected in combination with the Pourbaix diagram; electrochemical tests are performed on cemented carbide samples to obtain the overall and corrosion kinetics information of the cemented carbide, evaluate its corrosion resistance, and verify the corrosion resistance of the cemented carbide.
[0120] In a typical embodiment of the present invention, a corrosion-resistant multi-principal bonding phase cemented carbide is designed and the corrosion resistance of the cemented carbide sample is further verified. The composition and phase structure of the cemented carbide are fully considered, and the Pourbaix diagram is used to calculate and predict the corrosion products of the corresponding cemented carbide system, and the cemented carbide system that generates the target protective corrosion products is screened. The prediction results of the corrosion products of the WC-CoCrNi system correspond to the expansion of the immune zone and the generation of the passivation corrosion products Cr2O3 and NiO; Figure 3 As shown, the phase structure of the cemented carbide system was preliminarily screened by combining phase diagram calculation with first-principles calculation method. The phase diagram calculation results show that WC, FCC structure CoCrNi and corresponding metal carbides are generated in the corresponding sintering temperature and composition range. According to the selected phase structure combined with the phase diagram composition range, the design of experimental powder ratio is further guided. At the same time, the preparation method of powder metallurgy and electrochemical test corrosion resistance are combined. TEM is used to characterize the composition structure of the prepared cemented carbide, and micro-area electrochemical test is used to verify the galvanic corrosion characteristics of the hard phase and the bonding phase. The design and rationality and performance improvement of the prepared cemented carbide system are revealed through Pourbaix calculation, phase diagram calculation, experimental design, powder metallurgy, TEM, and micro-area electrochemical corrosion test, which is of great significance to the design of new corrosion-resistant multi-principal bonding phase cemented carbide.
[0121] The third aspect of the embodiment of the present invention also provides the application of the corrosion-resistant multi-primary bonding phase cemented carbide prepared by the above preparation method in the manufacture of marine drilling equipment. For example, according to the technical solution provided by the present invention, a corrosion-resistant multi-component bonding phase cemented carbide can be obtained, wherein the hard phase includes WC and the bonding phase includes CoCrNi, and the good coordination and low corrosion tendency between the two make it have excellent corrosion resistance and can be used in future drilling environments. More importantly, the verification conditions of the above corrosion-resistant multi-component bonding phase cemented carbide are also determined based on the above design method.
[0122] The technical solution of the present invention is further described in detail below through several embodiments and in conjunction with the accompanying drawings. However, the selected embodiments are only used to illustrate the present invention, and do not limit the scope of the present invention.
[0123] Example 1
[0124] This embodiment illustrates the overall process of designing and experimentally verifying a corrosion-resistant multi-principal-element binder phase cemented carbide, which is specifically as follows:
[0125] (1) Determine the type of alloying elements according to the target multi-principal bonding phase to obtain the target cemented carbide system;
[0126] (2) Establish a thermodynamic database for the target cemented carbide system;
[0127] (3) calculating the Pourbaix diagram of the W-Co-Cr-Ni system at different electrode potentials and pH values based on the thermodynamic database to obtain the immune zone and the passivation zone;
[0128] (4) calculating the cemented carbide phase diagram based on the thermodynamic database W-Co-Cr-Ni-C to obtain the composition intervals of different phase formations;
[0129] (5) Preparation of cemented carbide samples by powder metallurgy;
[0130] (6) Conduct structural characterization and corrosion performance testing on the prepared cemented carbide samples;
[0131] (7) Calculating the composition structure of the cemented carbide system based on the phase diagram of the thermodynamic database, and verifying the prepared cemented carbide system using TEM;
[0132] (8) The galvanic corrosion relationship between the hard phase and the bonding phase was measured using a micro-area electrochemical test method. The galvanic corrosion relationship was experimentally verified to reveal the differences in the corrosion resistance of cemented carbide.
[0133] Regarding the implementation details, in step (1), the type and composition of the multi-component bonding phase alloy elements are determined according to the corrosion resistance of the target cemented carbide; by consulting relevant cemented carbide and its related thermodynamic calculation literature, the wetting relationship between the hard phase and the bonding phase is fully considered, the electrochemical corrosion characteristics of the corresponding metal elements of the corresponding cemented carbide system are calculated, and a reasonable multi-component alloy is selected as the bonding phase to prepare the cemented carbide.
[0134] In step (2), the main steps of establishing the thermodynamic database of the target multi-component binder phase cemented carbide system are:
[0135] Step 2-1: Consult the literature to obtain specific thermodynamic data of binary, ternary and other low-element systems related to the target system, evaluate and screen the data in the literature, and discard unreliable data;
[0136] Step 2-2: According to the obtained phase diagram, thermodynamic experimental information and phase equilibrium conditions, combined with a suitable thermodynamic model, the adjustable parameters are determined, and then the appropriate parameter values are obtained by least squares optimization, and then the phase diagram and thermodynamic data are calculated using the obtained parameter values;
[0137] Step 2-3: Self-consistency verification, that is, from simple binary systems to complex multi-component systems, the phase diagram is calculated through the thermodynamic database to obtain the component structure corresponding to the target system, and the correction parameters are evaluated and optimized multiple times until a reliable and reasonable thermodynamic database of the target cemented carbide system is finally obtained.
[0138] Step 2-4: Use the established thermodynamic database of multi-element systems to draw a phase diagram with pressure, temperature and composition as variables. Different regions in the phase diagram correspond to different components and phase compositions. Based on the correspondence between performance and structure, the composition of corrosion-resistant cemented carbide can be reasonably designed according to the phase diagram, thereby preparing cemented carbide with the expected structure and performance.
[0139] In step (3), the Pourbaix diagram of the corresponding system is calculated using thermodynamic calculation and Nernst equation, the corrosion resistance of the cemented carbide system is predicted, and the composition of the corresponding multi-element alloy binder phase cemented carbide is screened;
[0140] Step 3-1: Calculate the Gibbs free energy of the target cemented carbide system elements after solid solution by combining the thermodynamic database and phase diagram calculation software Pandat;
[0141] Step 3-2: Based on the Gibbs free energy of the corresponding element, the corrosion Pourbaix diagram of the corresponding system is calculated in combination with the Nernst equation. The Pourbaix diagram calculation process is to select the elements involved in the system, input the electrode potential range and temperature parameters, and output all possible products; after selecting and optimizing the products, a single-element Pourbaix diagram is generated, and the different single-element Pourbaix diagrams obtained by the above method are superimposed to obtain the Pourbaix diagram of the target system.
[0142] In step (4), the main steps to select a reasonable system phase interval are:
[0143] Step 4-1: Calculate the cemented carbide system phase diagram;
[0144] Step 4-2: Calculate the composition range of different carbon contents of cemented carbide system under different conditions according to the phase diagram;
[0145] Step 4-3: Determine the liquid phase sintering temperature and the corresponding sintering range based on the relationship between the phase structure, carbon content and temperature obtained from the phase diagram calculation results.
[0146] In step (5), a cemented carbide sample is prepared by a powder metallurgy method, the steps of which are:
[0147] Step 5-1: Determine the corresponding ratio of WC to the multi-principal alloy binder phase CoCrNi and the system carbon supplementation content according to the calculated phase interval;
[0148] Step 5-2: The ball-to-material mass ratio during wet milling is 8:1 to 12:1, and the ball milling time is 10 to 20 hours;
[0149] Step 5-3: The pressing pressure during the pressing process is 120 to 180 MPa;
[0150] Step 5-4: The temperature of liquid phase sintering is determined according to the phase diagram, and the time of liquid phase sintering is 1 to 2 hours;
[0151] Step 5-5: Combine the sample after liquid phase sintering with the phase diagram to obtain a cemented carbide in the corresponding phase range.
[0152] In step (6), the prepared cemented carbide sample is subjected to structural characterization and corrosion performance testing, the steps of which are:
[0153] Step 6-1: Prepare the sample and grind and polish the sample surface to meet the requirements of subsequent morphology test and electrochemical corrosion test;
[0154] Step 6-2: Use TEM to verify the structural composition of the designed cemented carbide; perform TEM tests on the prepared samples to characterize the internal structure and composition of the samples, and compare the corresponding intervals obtained by the phase diagram calculation design to verify the rationality of the phase diagram calculation prediction design.
[0155] In step (7), the prepared cemented carbide sample is subjected to a micro-area electrochemical corrosion test, the steps of which are:
[0156] Step 7-1: Place the prepared electrochemical sample in a micro-area electrochemical device for regional scanning to characterize the micro-area and the microscopic electrochemical corrosion performance of the corresponding different components, and characterize the corrosion resistance of the corresponding multi-component alloy bonding phase. Reveal the difference in corrosion resistance between different components at the micron scale.
[0157] Step 7-2: The sample surface was subjected to SVET (scanning vibration electrode test) test and LEIS (micro-area electrochemical impedance spectroscopy) test respectively. The micro-area electrochemical characterization results showed that the hard phase and bonding phase in the cemented carbide system had different corrosion current density and electrochemical impedance, which verified the galvanic corrosion effect and also reflected that the WC-CoCrNi system had better corrosion resistance.
[0158] Step 7-3: The current density and impedance information show the difference distribution between the hard phase and the bonding phase, verifying the galvanic corrosion effect on its surface. At the same time, the low corrosion current density and high impedance value of the bonding phase characterize the excellent corrosion resistance of the corresponding system.
[0159] Of course, the specific processes, means and items of material preparation and material characterization testing may be different from the above-mentioned examples. All modified implementation methods that utilize the main design ideas are within the scope of the present invention.
[0160] Example 2
[0161] This embodiment uses the technical solution provided in Example 1 to illustrate a design method for a WC-CoCrNi corrosion-resistant multi-principal element bonding phase cemented carbide, as shown below:
[0162] 1. Determine the type and composition of alloy elements according to the corrosion resistance of the target cemented carbide; by consulting relevant corrosion-resistant cemented carbide and its design-related literature, fully consider the wetting relationship between the hard phase and the bonding phase, and select a reasonable multi-principal alloy bonding phase to prepare the cemented carbide. Because the prepared cemented carbide requires good corrosion resistance, the W-Co-Cr-Ni-C quinary system is selected as the target cemented carbide preparation in combination with literature research.
[0163] 2. Consult the literature to obtain thermodynamic data related to the target system; the thermodynamic data of the known systems in this system are: based on the collected binary, ternary and even quaternary databases of C-Co, C-Cr, CW, Co-W, Cr-W, C-Co-Cr, Co-Cr-W, C-Co-W, C-Ni-W, C-Co-Ni-W, etc., integrate them through the CALpHAD method based on the thermodynamic database, draw the phase diagram through the Thermo-Ca1c software and verify the accuracy of the low-element database, compare the combined phase diagram with the original phase diagram, continue to consult the literature for correction until the drawn phase diagram is accurate; repeat the above verification process until the thermodynamic database of the W-Co-Cr-Ni-C quinary system is obtained.
[0164] 3. Pourbaix diagram calculation is performed based on the thermodynamic database, and the Pourbaix diagram of the corresponding system is calculated in the W-Co-Cr-Ni system using thermodynamic calculation and Nernst equation, and the immune zone and passivation zone of the above system are obtained, and the corrosion tendency is compared with the classic W-Co system. Based on the thermodynamic database, using the Nernst equation, taking the pure element Gibbs free energy as the benchmark, the energy difference of each element in the target component is obtained through the electrochemical reaction equation and the Nernst equation and converted into a potential difference value to evaluate the galvanic corrosion tendency.
[0165] 4. Based on the thermodynamic database, the cemented carbide phase diagram is calculated using the phase diagram calculation software Pandat, and the ratio of the hard phase to the binder phase is fixed, and the carbon content of the system is changed to obtain a vertical interface phase diagram, wherein the content of the hard phase WC is 80wt.%, and the content of the binder phase CoCrNi is 20wt.%; the composition intervals generated by various different phases are calculated in the multi-element alloy system, and the guiding interval is screened based on the composition interval and its corresponding phase structure.
[0166] 5. Use powder metallurgy to prepare gold cemented carbide.
[0167] According to the expected structure of the binder phase, the composition range of the required binder phase is determined in combination with the phase diagram, and the powder ratio is carried out according to the composition in this range.
[0168] By adding in the binder phase powder and the hard phase powder for high energy ball milling;
[0169] Mix 80% WC powder by mass with 20% CoCrNi and a trace amount of carbon black powder; add carbide grinding balls, wherein the ball-to-material mass ratio is 10:1, and add ball milling medium alcohol, and the ball milling time is 16 hours;
[0170] The mixed slurry after ball milling was dried and sieved, and then the pressing pressure in the pressing process was 150MPa;
[0171] The crushing sintering temperature was 1450°C and kept at this temperature for 90 min to obtain the cemented carbide sample;
[0172] 6. Conduct structural verification and corrosion resistance testing on the manufactured cemented carbide.
[0173] TEM was used to verify the composition and phase structure of the designed cemented carbide;
[0174] By selecting a simulated drilling fluid with a pH value of 10 as the electrolyte, in the hope of being applied in a drilling environment, a corrosion experiment was conducted at 25°C using the electrochemical three-electrode technique.
[0175] Combined with the micro-area electrochemical test results, the galvanic corrosion differences and corrosion resistance of the sample surface are revealed, and the corrosion products on the sample surface calculated by Pourbaix and the corresponding corrosion resistance improvement are verified.
[0176] 7. Micro-area electrochemical experiments are used to experimentally verify the galvanic corrosion tendency.
[0177] The SVET technique was used to test the local corrosion current of the hard phase and the bonding phase plane, and the current difference between the hard phase and the bonding phase of the WC-CoCrNi and WC-Co samples was compared to intuitively obtain the corrosion rate between the hard phase and the bonding phase.
[0178] The LEIS technology was used to test the local corrosion impedance of the hard phase and bonding phase planes. The impedance values between the hard phase and bonding phase of WC-CoCrNi and WC-Co samples were compared respectively to intuitively obtain the corrosion resistance between the hard phase and bonding phase.
[0179] Based on the above embodiments, it can be clearly seen that the technical solution provided in the embodiments of the present invention, through the establishment of a thermodynamic database and a method based on Pourbaix calculation and phase diagram calculation, combined with a unique means of micro-area electrochemical characterization of the corrosion resistance of cemented carbide, evaluates and selects the basic characteristics and corrosion resistance of the bonding phase, obtains the optimal bonding phase composition structure corresponding to the cemented carbide system, and matches the optimal test conditions, thereby obtaining a closed loop between the design, preparation, and verification of multi-principal component corrosion-resistant cemented carbide materials. The provided design method can clarify the type of corrosion-resistant bonding phase, use Pourbaix diagram calculation and phase diagram calculation to guide the design of a reasonable cemented carbide preparation process, improve the research and development efficiency of corrosion-resistant cemented carbide, and enhance the understanding of the relationship between cemented carbide phase structure and performance through TEM testing and micro-area electrochemical verification.
[0180] The composition and structure of the system corresponding to the phase diagram calculation were obtained by TEM testing of the prepared cemented carbide, indicating the efficiency and rationality of the phase diagram calculation design of cemented carbide. Figure 4a-4g The TEM results shown show that the composition structure in the corresponding cemented carbide system is consistent with the predicted results of phase diagram calculation. Figure 4a and Figure 4e The high-angle annular dark field (HAADF) images of two different regions inside WC-CoCrNi were characterized respectively. As shown in the figure, W elements and C elements are enriched in the WC region, and the elements contained in the CoCrNi binder phase are enriched in the binder phase region. Figure 4b and Figure 4f The high-resolution TEM (HR-TEM) images at the interface between WC and CoCrNi were characterized respectively, and the interplanar spacing of the WC hard phase was measured to be 0.25 nm, corresponding to the (100) crystal plane, and the d spacing of the CoCrNi bonding phase was 0.20 nm, corresponding to the (111) crystal plane. Figure 4c , 4d 4g and 4g are the selected area electron diffraction (SAED) patterns of CoCrNi binder phase, WC hard phase, and Cr3C, respectively, characterizing the FCC structure of CoCrNi binder phase and the HCP structure of WC particles. The TEM characterization results show the high efficiency and rationality of phase diagram calculation design of cemented carbide.
[0181] Combined with micro-area electrochemical technology, the microscopic corrosion kinetics information can be detected, which is convenient for intuitive comparison of the bonding phase type and cemented carbide system with excellent corrosion resistance. The corrosion test results are as follows: Figure 5a-5d shown.
[0182] It should be understood that the above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.
Claims
1. A design method for corrosion-resistant multi-principal-element bonding phase cemented carbide, characterized in that: include: Obtaining a target corrosive service environment, and formulating a target cemented carbide system according to the target corrosive service environment, wherein the target cemented carbide system includes a hard element corresponding to hardness and a bonding element corresponding to bonding; Establishing a phase diagram thermodynamic database of the target cemented carbide system; According to the phase diagram thermodynamic database, a Pourbaix diagram is calculated for the target cemented carbide system to obtain the inferred corrosion products of the target cemented carbide system under the target corrosive service environment and the immune zone and the passivation zone corresponding to the inferred corrosion products, and a multi-principal alloy is selected as a bonding phase from the bonding elements; According to the phase diagram thermodynamic database, a phase diagram is calculated for the target cemented carbide system to obtain phase composition and phase parameters, wherein the phase composition includes the ratio of the bonding elements and the ratio of the hard phase to the bonding phase, and the phase parameters include heat treatment temperature; The multi-principal component alloy, phase composition and phase parameters are used as design outputs of the corrosion-resistant multi-principal component bonding phase cemented carbide.
2. The design method according to claim 1, characterized in that: The hard elements include any combination of W, Ti, C, and N; And / or, the bonding element includes any combination of Co, Cr, Ni, Fe, Al, and Mn.
3. The design method according to claim 1, characterized in that: The selection rules of the multi-principal alloy specifically include: Selecting the required element types and proportions of the hard phase and the binder phase according to the target corrosive service environment; The immune zone and passivation zone of the system are obtained by calculating the Pourbaix diagram. The immune zone is the non-corrosion zone of the thermodynamically stable state below the equilibrium line of the Pourbaix diagram; the passivation zone is the corrosion product zone where oxides and hydroxides are generated. The corrosion product film has a certain protective effect to reduce corrosion. In some embodiments, the selection rules of phase composition and phase parameters specifically include: Calculating a phase diagram according to the target cemented carbide system composition; Select the area of normal structure WC+γ of cemented carbide based on the phase diagram calculation results; When the phase diagram calculation results show that there is no region containing only WC+y, the region with the C content closest to the transition line from the carbon-poor phase to the graphite phase is selected; The liquidus of the target cemented carbide system is determined based on the phase diagram calculation result, and the sintering temperature is determined based on the liquidus.
4. The design method according to claim 1, characterized in that: The process of establishing the phase diagram thermodynamic database specifically includes: Acquiring thermodynamic data of a low-element system, wherein the elements in the low-element system are part of the elements in the target cemented carbide system; Establishing a thermodynamic model to calculate the Gibbs free energy of multiple phases in the low-element system; All calculation results are integrated and expanded to form a phase diagram thermodynamic database of the target cemented carbide system.
5. The design method according to claim 1, characterized in that: The process of calculating the Pourbaix diagram specifically includes: Importing the phase diagram thermodynamic database into the calculation software, using the point calculation module to input the target composition of the target cemented carbide system, and obtaining the chemical potential corresponding to each element in the target composition; Based on the Gibbs free energy of pure elements, the energy difference of each element in the target component is obtained through the electrochemical reaction equation and the Nernst equation and converted into a potential difference value; A multivariate Pourbaix diagram is obtained based on superimposed pure element Pourbaix diagrams, the change in Gibbs free energy caused by alloying is calculated, and the immune area and the passivation area of the multivariate Pourbaix diagram are delineated.
6. The design method according to claim 1, characterized in that: Also includes: Preparing verification samples according to the multi-principal alloy, phase composition and phase parameters by powder sintering; The microstructure and corrosion pattern of the verification samples are characterized to verify the effectiveness of the design output.
7. The design method according to claim 6, characterized in that: The characterization method of the microscopic morphology includes transmission electron microscope observation, and the characterization method of the corrosion mode includes micro-area electrochemical experiment.
8. A method for preparing a corrosion-resistant multi-principal-component bonding phase cemented carbide, characterized in that: include: Using the design method described in any one of claims 1 to 7 to obtain the design output in the target corrosive service environment; According to the design output, a corrosion-resistant multi-principal-component bonding phase cemented carbide is prepared.
9. The preparation method according to claim 8, characterized in that: Specifically include: preparing a binder phase powder and a hard phase powder according to the design output; The mixed powder is prepared according to the ratio of the hard phase and the binder phase outputted in the design, and ball milling and pressing are performed to obtain a sintered hard alloy block; The cemented carbide block sintered blank is subjected to vacuum sintering to obtain the corrosion-resistant multi-principal-element bonding phase cemented carbide.
10. Use of the corrosion-resistant multi-principal-component binder phase cemented carbide prepared by the preparation method according to any one of claims 8 to 9 in the manufacture of marine drilling equipment.
Citation Information
Patent Citations
WC-Co hard alloy and preparation method thereof
CN101974715A
Method for improving corrosion resistance of WC-Co hard alloy
CN102031436A
preparation method of a Fe-Cu-C alloy material with predetermined hardness
CN109657382A
Research method of rare earth modified WC-CoFeNi composite binding phase alloy
CN116312889A
Hard sintered body, method for producing hard sintered body, cutting tool, wear-resistant tool and high-temperature member
JP2023048855A
Cited By
Design / preparation method for corrosion-resistant cemented carbide with multi-principal-element binder phase, and use of same
WO2026092175A1